Izzivi uporabe visoko-pretočnega sekvenciranja (HTS) za rutinsko diagnostiko viroidov - Guček, Tanja (Hmeljarski bilten, 2025)
Viroid diseases pose a continual threat to global agriculture, as these small and structurally simple pathogens are capable of infecting a wide range of economically important plant species. Effective prevention and management of viroid infections therefore require diagnostic approaches that ensure reliable, sensitive, and specific identification of the causal agents. Advances in biochemistry and molecular biology have, in recent years, significantly improved the sensitivity and specificity of many diagnostic methods. With decreasing sequencing costs and increasing accessibility, interest in the use of high-throughput sequencing (HTS) in routine plant diagnostics has grown rapidly. Despite the great potential of HTS, the implementation of these technologies into laboratory practice remains challenging. Key obstacles include the selection of an appropriate sequencing platform and laboratory protocols, the use of suitable bioinformatic tools, the availability of adequately trained personnel, and the establishment of suitable computational infrastructure. Although certain standards and guidelines for HTS have already been developed, they are not universally applicable due to the specific needs of individual laboratories. This review article discusses the key aspects of different HTS approaches, their advantages and limitations, and illustrates their applicability using the example of viroid disease diagnostics.
Keywords: bioinformatics; bioinformatika; diagnostics; diagnostika; high-throughput sequencing (HTS); nanopore tehnologija (ONT); Oxford Nanopore technology (ONT); viroidi; viroids; visoko-pretočno sekvenciranje (HTS)